Resolute Readings of Wittgenstein and Nonsense - Joseph Ulatowski (Journal for the History of Analytical Philosophy, 2020)
The aim of this paper is to show that a corollary of resolute readings of Wittgenstein’s conception of nonsense cannot be sustained. First, I describe the corollary. Next, I point out the relevance to it of Wittgenstein’s discussion of family resemblance concepts. Then, I survey some typical uses of nonsense to see what they bring to an ordinary language treatment of the word “nonsense” and its relatives. I will subsequently consider the objection, on behalf of a resolute reading, that “nonsense” is a term of philosophical criticism. Finally, I conclude that resolute readings have not sufficiently accounted for how nonsense behaves in our language; they have failed to heed Wittgenstein’s warning: “don’t think, but look!”